AUTOMATING MEDICAL INSURANCE CLAIMS PROCESSING WITH AWS CLOUD, BIG DATA, AND ANALYTICS - Chandrasekhar Katasani (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The healthcare insurance sector is experiencing a transformative shift through the integration of cloud computing and big data technologies, particularly in claims processing automation. This paper examines the implementation of AWS Cloud services and big data analytics in medical insurance claims processing, highlighting the significant improvements in operational efficiency, cost reduction, and customer satisfaction. The article presents a comprehensive analysis of key components in claims automation, including data ingestion, validation, fraud detection, and analytics, while demonstrating how cloud-based architectures have revolutionized traditional claims processing workflows. The article provides insights into the advantages of AWS implementation and presents a detailed architectural framework for building robust claims automation systems that meet contemporary healthcare demands.